Injection molding using a novel binder system based on palm oil derivatives - Abu Talib, Abd. Rahim; Ibrahim, Rosdi; Ahmad, Mohamad Azmirruddin; Suleiman, Muhammad Jabir; Johari, Nurhaslina (2013)
There is disclosed an injection molding using a binder system based on palm oil derivatives, wherein the method of producing components suitable for aerospace applications, the components are manufactured from super alloy material, where the method comprises the steps of mixing super alloy with a binder materials, injecting a mixture into desired shape mold, de-binding the binder according a process of melting and evaporation temperature of the binders, sintering of the de-bound part in a High Temperature Control Atmosphere Furnace, heating the de-bound part at highest temperature to its melting temperature and soaking the de-bound part into required duration of time.